1997
DOI: 10.1200/jco.1997.15.8.2920
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy for stage II and stage III pancreatic carcinoma.

Abstract: Palliation and survival compare favorably with other series, including many surgical series. The response findings encourage studies of both unresectable and (as neoadjuvant therapy) resectable tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(27 citation statements)
references
References 30 publications
0
24
0
3
Order By: Relevance
“…Recent trials of preoperative chemoradiation have been conducted at Fox Chase Cancer Center (including the Eastern Cooperative Oncology Group phase II trial), 26 -29 The M. D. Anderson Cancer Center, 7,30,31 New England Deaconess/Dartmouth Medical Centers, 32,33 Roger Williams Cancer Center, 34,35 and the Mount Sinai Hospital. 36 While employing different regimens of chemotherapy and radiotherapy (including intraoperative radiotherapy at M.D. Anderson), these trials have each reported surgical complication and mortality rates similar to those of patients without preoperative treatment and lower rates of local recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Recent trials of preoperative chemoradiation have been conducted at Fox Chase Cancer Center (including the Eastern Cooperative Oncology Group phase II trial), 26 -29 The M. D. Anderson Cancer Center, 7,30,31 New England Deaconess/Dartmouth Medical Centers, 32,33 Roger Williams Cancer Center, 34,35 and the Mount Sinai Hospital. 36 While employing different regimens of chemotherapy and radiotherapy (including intraoperative radiotherapy at M.D. Anderson), these trials have each reported surgical complication and mortality rates similar to those of patients without preoperative treatment and lower rates of local recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Response rates varied between 39% and 47%, with a median survival time of 14-15.5 months [4,[30][31][32]. The resectability rate was 10.5%, using combined radiochemotherapy with 5-FU, leucovorin, and mitomycin [30], and 14.2% after 5-FU, streptozotocin, and cisplatin, with simultaneous split-course radiotherapy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the high rate of recurrence, surgery alone seems to be inadequate for the treatment of patients with pancreatic cancer. Indeed, new clinical approaches such as, for example adjuvant chemotherapy plus radiation therapy (chemoradiation) after surgery or before surgery have been attempted and only a little improvement was observed in the survival rates of patients with pancreatic cancer, but the prognosis has remained worse than other cancers, such as breast cancer, colon cancer and gastric cancer (Ozaki et al, 1996;Schnall et al, 1996;Kamthan et al, 1997). In addition, most patients with pancreatic cancers are already unresectable when they are initially diagnosed.…”
Section: Discussionmentioning
confidence: 99%